Régénération artificielle du chêne-liege et équilibre climacique de la subéraie en forêt de la Mamora - Lepoutre, B (Annales de la Recherche Forestiere au Maroc, 1967)
In order to determine the edaphical conditions, which warrant a successful artificial regeneration of the cork-oak in the Mamora forest, the author passes in review previous inquiries and to begin points out material already learned on this problem. After giving a quick glance at the nature of soils constituted by a sandy cover of variable depth (0,40 to 6 ni) on an antique argillaceous- sandy deep formation, the author firstly puts forward the obviousness of the harmful influence of the considerable sand depths on the artificial regeneration of the cork-oak in the western Mamora. Inversely, he shows that a successful regeneration is as surely secured when the deep argilla- ceous-sandy formation called (( Mamora red clay D is closer to the surface. At this juncture, he manages to specify that the depth of sand over two meters is incompatible with the growth of cork-oak seedlings, but that the latter is subject to variations in cases where clay is close to the surface. The analysis of these variations enables the detection of a new factor of a favourable issue, which can be defined by the intensity of the side draining, the best outcome being under the conditions of a medium side-draining. Leaving the western Mamora with its more humid climate, the author continues his investigations in the semi-arid central Mamora. Generally, the soils are here less deep and the side-draining appears as a determinant factor in a favourable outcome or a failure of artificial cork-oak sowings. On flat or slighty sloping grounds the zones of failures fall in with localizations of perched winter phreatic sheets. The mechanical action of these sheets is studied parallelly with the nature of the cultural profile and the cork-oak rooting. Then, it becomes evident that the young cork-oak is unable to hold its ground during summer unless its radicular system succeeded to settle in the deep clay during the winter. On a sloping ground, the author comes to consider the depth of the sand as a vertical component of the draining and couples it with the horizoiztal component represented by the slope. Every sowing inventory site can be defined in this way through its draining characteristics and be graphically shown in relation to two axis of rectangular co-ordinates, bearing respectively, the slope on the absciss and the depth on the ordinate. Then, in applying to each inventory site a criterion for the growth of a sowing, the author comes to set up a diagram showing on one hand, the relationship between the good issue or the failure, and on the other hand, the draining. The study of the said diagram provides esential laws of repartition of successful issues and failures in the artificial regeneration. This method of study being applied to the even more arid oriental Mamora brings forward new results, while it warrants replacing the results of western Mamora into the same ecological scope. Comparing the three climatic sectors, it becomes possible to introduce climate as a factor in the interpreting of the results and, finally, to determine the edaphical climatic conditions of cork-oak regeneration in Mamora forest. This successful method, which seems to supply essential ecological elements to determine the installation and the growing of young cork-oaks leads the author to follow up his investigations, this time in the adult cork-oak forest, making evident the laws of the repartition of the forest dependent on draining, but, where he also shows the link between the density and the age of the stump range on one hand, and the edapho- climatic conditions on the other hand. Finally this study ends at the equilibrium of the climax in the cork-oak The synthesis warrants, in fact, comparing the previous conditions of the installation of the cork-oak, the more recent and the present one, by means of studies, respectively of old trees, young pole stage, and artificial regeneration. forest. Thereupon conclusions can be obtained in two fields. On the practical plan, the author lays down a correlation between the conditions of cork-oak artificial sowing and the density or the state of an adult forest. This correlation is the key to interpret the air photogra- phic covering in view of artificial regeneration and enables to ground a new management, based on extremely precise rules. On the ecological plan, the author is able to determine accurately the evolution of the forest, an evolution expressed by three natural states related to edapho-climatic conditions. The first state, where the regressive dynamism of the afforestation is observed by the presence of very old trees and where sowing is ineffective ; it is the old thin forest on deep sands or steep slopes. The second, where, on the contrary, exists a progressive dynamism of afforestation ; there are no trees, but empty spaces are conquered by young seedlings or by successful artificial regenerations. The third, where the equilibrium of the forest is secured by a strong density and a younger age of individuals, combined with the possibility of artificial or natural sowing. The author suggests for these three states the following denominations : postclimax, preclimax and euclimax, which would subdivide the general notion of climax as commonly used, and in which the existence of ecological equivalents forbids in any case the dissociation of edaphical factors and climatic conditions. He notes the interest of this notion of climax equilibrium in the scope of forestry management and, finally, underlines the parallelism of these conclusions with the one of his previous works, asserting a present seasonal climatic evolution in Morocco.
Keywords: chêne-liège; conditions édaphiques; drainage (voyant); épaisseur des sables; Mamora; Regeneration; réussite des semis; semis; semis artificiels